Coping, schemas, and cardiovascular risks – study protocol - Slepecky M (Dove Medical Press, 2017)
Milos Slepecky,1 Antonia Kotianova,1 Jan Prasko,2 Ivan Majercak,3 Erika Gyorgyova,4 Michal Kotian,1,5 Marta Zatkova,1 Ingrid Tonhajzerova,6,7 Michaela Chupacova,1,5 Marta Popelkova1 1Department of Psychology Sciences, Faculty of Social Science and Health Care, Constantine the Philosopher University in Nitra, Nitra, Slovak Republic; 2Department of Psychiatry, Faculty of Medicine and Dentistry, University Palacky Olomouc, University Hospital Olomouc, Olomouc, Czech Republic; 31st Department of Internal Medicine, Faculty of Medicine, Pavol Josef Safarik University in Košice, 4Internal Medicine and Cardiology Private Practice MUDr Ivan Majercak, Košice, 5Psychagogia, Liptovsky Mikulas, 6Department of Physiology, 7Biomedical Center Martin, Jessenius Faculty of Medicine in Martin, Comenius University in Bratislava, Martin, Slovak Republic Abstract: The aim of this article is to describe the protocol of a trial focusing on the psychological, anthropometric, cardiac, and psychophysiological factors contributing to increased risk of cardiovascular diseases (CVDs). As background, the article provides a short overview of research literature linking personal traits, maladaptive schemas, and coping styles with CVDs through reactivity of the autonomic nervous system. Keywords: early maladaptive schemas, coping styles, personality traits, dissociation, heart rate variability